Reprint ‒ Ureteral stent vs. no ureteral stent for ureteroscopy in the management of renal and ureteral calculi: A Cochrane review - Ordonez, Maria; Hwang, Eu Chang; Borofsky, Michael; Bakker, Caitlin J.; Gandhi, Shreyas; Dahm, Philipp (Canadian Urological Association Journal, 2019)
Introduction: We aimed to assess the effects of postoperative ureteral stent placement after uncomplicated ureteroscopy. Methods: We performed a comprehensive search with no restrictions on publication language or status up to February 1, 2019. We only included randomized trials. Two review authors independently examined full-text reports, identified relevant studies, assessed the eligibility of studies for inclusion, extracted data, and assessed risk of bias. We performed statistical analyses using a random-effects model and assessed the certainty of the evidence according to GRADE. Results: We included 23 studies with 2656 randomized patients. Primary outcomes: It is uncertain whether stenting reduces the number of unplanned return visits (very low certainty of evidence [CoE]). Pain on the day of surgery is probably similar (mean difference [MD] 0.32; 95% confidence interval (CI) -0.13‒0.78; moderate CoE). Pain on postoperative days 1‒3 may show little to no difference (standardized mean difference [SMD] 0.25; 95% CI -0.32‒0.82; low CoE). It is uncertain whether stented patients experience more pain on postoperative days 4‒30 (very low CoE). Stenting may result in little to no difference in the need for secondary interventions (risk ratio [RR] 1.15; 95% CI 0.39‒3.33; low CoE). Secondary outcomes: We are uncertain whether stenting reduces the need for narcotics and reduces ureteral stricture rates up to 90 days (very low CoE). Rates of hospital admission may be slightly reduced (RR 0.70; 95% CI 0.32‒1.55; low CoE). This review was limited to patients in whom ureteroscopy was deemed ‘uncomplicated.’ In addition, time intervals for the grouping for the reported degree of pain were established post-hoc. The CoE for most outcomes was rated as low or very low for methodological reasons. Conclusions: Findings of this review illustrate the tradeoffs of risks and benefits faced by urologists and their patients when it comes to decision-making about stent placement after uncomplicated ureteroscopy for stone disease.